Resource stock, age structure, and seed prediction of ferula sinkiangensis K.M. Shen - Wang, Qin; Dong, Hegan; Liu, Zhongquan; Chen, Baoxiong; Yu, Yang; Chen, Muhua (Bangladesh Journal of Botany, 2024)
Ferula sinkiangensis K.M. Shen (FS) is an endemic species in Xinjiang, China. It has extremely high economic and medicinal value but is on the brink of extinction. A comprehensive survey of the distribution area of FS was conducted to study its resource stock, age structure and yielding capacity of seeds. Results show that there is one existing distribution area of FS with an area of 322.84 hm2 and a total plant quantity of 907,100. The age structure of FS population is reasonable showing a growing type of population. After low-temperature treatment and indoor germination of the seeds of FS, the utilization efficiency of seeds was increased by 15.45 times and 1165.81 times respectively. The establishment of the original habitat protection zone has played a huge role in promoting the recovery of the population of FS and the indoor germination of seeds would greatly alleviate the problem of seeds shortage of FS. Bangladesh J. Bot. 53(3): 765-772, 2024 (September) Special